Tantangan Profesionalisme Guru pada Era Globalisasi - Luluk Indarinul Mufidah (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2019)
The profession as an educator is a profession that requires qualifications. One of the competencies of educators is to understand the child's development in supporting the learning process in the classroom. A teacher is a professional educator, so implicitly a teacher has volunteered himself to assume some of the educational responsibilities of the parents of students. Not everyone can become a teacher, because the teaching profession requires professionalism, prioritizing social interests and sincerity in carrying out tasks. All educators can become professional as long as there is intention, desire, motivation and commitment to do and achieve it. To realize high professionalism, educators can partner with the best people and organizations from all over the world. In addition, professional mentality must be possessed by professionals, namely quality mentality, altruistic mentality, service mentality, learner mentality, service mentality, creative mentality, and ethical mentality.